Coherent Seasonal Acceleration of the Weddell Sea Boundary Current System Driven by Upstream Winds - Le Paih, Nicolas; Hattermann, Tore; Boebel, Olaf; Kanzow, Torsten; Lüpkes, Christof; Rohardt, Gerd; Strass, Volker; Herbette, Steven (Journal of Geophysical Research: Oceans, 2020)
The Weddell Sea is of global importance in the formation of dense bottom waters associated with sea ice formation and ocean-ice sheet interaction occurring on the shelf areas. In this context, the Weddell Sea boundary current system (BCS) presents a major conduit for transporting relatively warm water to the Weddell Sea ice shelves and for exporting some modified form of Wedell Sea deep and bottom waters into the open ocean. This study investigates the downstream evolution of the structure and the seasonality of the BCS along the Weddell Sea continental slope, combining ocean data collected for the past two decades at three study locations. The interannual-mean geostrophic flow, which follows planetary potential vorticity contours, shifts from being surface intensified to bottom intensified along stream. The shift occurs due to the densification of water masses and the decreasing surface stress that occurs westward, toward the Antarctic Peninsula. A coherent along-slope seasonal acceleration of the barotropic flow exists, with maximum speed in austral autumn and minimum speed in austral summer. The barotropic flow significantly contributes to the seasonal variability in bottom velocity along the tip of the Antarctic Peninsula. Our analysis suggests that the winds on the eastern/northeastern side of the gyre determines the seasonal acceleration of the barotropic flow. In turn, they might control the export of Weddell Sea Bottom Water on seasonal time scales. The processes controlling the baroclinic seasonality of the flow need further investigation.
Keywords: Sørishavet; Weddellhavet; batymetri; havstrømmer; innlandsis; kontinentalmargin; oseanografi

Volcanic passive continental margin beneath Maitri station in central DML, East Antarctica: constraints from crustal shear velocity through receiver function modelling - Gupta, Sandeep; Kanna, Nagaraju; Akilan, A (Polar Research, 2017)
Dronning Maud Land (DML) in East Antarctica is considered to be a key area for the reconstruction of the Gondwana supercontinent. We investigate the crustal shear wave velocity (Vs) model beneath the Maitri station, situated in the central DML of East Antarctica, through receiver function modelling. The analysis shows an average crustal thickness of 38.50 ± 0.5 km and a Vp/Vs ratio of 1.784 ± 0.002. The obtained Vs structure suggests that the topmost ca. 2.5 km of the crust contains ice and sediments with low Vs (1.5–2.0 km/s). This layer is underlain by a thick (ca. 12.5 km) layer of Vs = 2.25–2.6 km/s, suggestive of an extrusive igneous rock (rhyolite) at this depth range. Between 16 and 28 km depth, the Vs increases from 2.9 to 3.4 km/s. In the lower crust, a 7 km thick layer of Vs = 3.9 km/s is followed by 6 km thick underplated layer (Vs = 4.1 km/s) at the crust–mantle boundary. The uppermost mantle Vs is ca. 4.3 km/s. With the observation of underplated material in the lowermost crust, extrusive volcanic rocks in the upper crust, seaward dipping reflectors in the surrounding and a general paucity of seismicity, we believe the crust beneath the Maitri station represents a volcanic passive continental margin. We also believe that after its origin in the Precambrian and during its subsequent evolution it might have been affected by the post-Precambrian tectono-thermal event(s) responsible for the Gondwana supercontinent break-up.
Keywords: Dronning Maud Land; geofysikk; kontinentalmargin; seismologi; tektonikk; vulkaner

Reassembling Gondwana: A new high quality constraint from vibroseis exploration of the sub-ice shelf geology of the East Antarctic continental margin - Kristoffersen, Yngve; Hofstede, Coen; Diez, Anja; Blenkner, Richard; Lambrecht, Astrid; Mayer, Christoph; Eisen, Olaf (Journal of Geophysical Research: Solid Earth, 2014)
The breakup of Gondwana is manifested by coeval early Jurassic Karoo magmatism in South Africa and East Antarctica. In South Africa, the large volumes of volcanic rocks of the adjoining Lebombo and Mwenetzi-Save monoclines represent a volcanic rift margin, and in East Antarctica, a corresponding feature, the Explora Wedge is buried below sediments and floating ice shelves on the continental margin of Dronning Maud Land. We use the seismic vibrator source to explore the sub-ice geology in Antarctica, and the new seismic reflection and available regional aeromagnetic data enable us to outline a dogleg landward extent of the Explora Wedge in Dronning Maud Land. The congruent inboard wedge geometries on the two continents define a high quality constraint, which facilitate for the first time, a geologically consistent and tight reconstruction of Africa relative to East Antarctica within Gondwana. The uncertainties in correlations of major geological features (mobile belts) from one continent to the other may now be of the order of ten's of kilometers rather than hundreds of kilometers.
Keywords: Antarktis; geofysikk; geologi; kontinentalmargin; seismologi; stratigrafi

Sources and geographic heterogeneity of trace metals in the sediments of Prydz Bay, East Antarctica - Sun, Wei-Ping; Hu, Chuan-Yu; Weng, Huan-Xin; Han, Zheng-Bing; Shen, Chen; Pan, Jian-Ming (Polar Research, 2013)
In this study, we have determined the contents and distribution of zinc and cadmium in the surface sediments from Prydz Bay, East Antarctica. The main sources of the trace elements and their geographic heterogeneity, and the relation between Zn and Cd, are discussed based on the cluster analysis, principle component analysis and considerations of biogenic and lithogenic inputs. The results show that the contents of trace metals range from 34.6 to 96.6 mg kg-1 for Zn, and from 0.254 to 0.441 mg kg-1 for Cd. Calculations of the enrichment factor indicated no significant anthropogenic impact. Biogenic and lithogenic inputs are the main sources of trace metals. They are almost equal for Zn and Cd at the Amery Ice Shelf edge, while the continental shelf and deep ocean are dominated by biogenic inputs. The contribution of biogenic inputs is much higher for Zn than for Cd at the deep ocean. Calculations of biogenic trace metals revealed different relationships between biogenic Zn and biogenic Cd, which reflect the biological uptake by phytoplankton in the water column. Keywords: Trace elements; sources; enrichment factor; cluster analysis; principal component analysis; Antarctica.
Keywords: Sørishavet; fytoplankton; geografi; kjemiske analyser; kontinentalmargin; kontinentalsokkel; marin biologi; oseanografi; sedimenter; sedimentologi

Observations of the Antarctic Slope Undercurrent in the southeastern Weddell Sea - Chavanne, Cédric P; Heywood, Karen J; Nicholls, Keith W; Fer, Ilker (Geophysical Research Letters, 2010)
The Antarctic Slope Front presents a dynamical barrier between the cold Antarctic shelf waters in contact with ice shelves and the warmer subsurface waters offshore. Two hydrographic sections with full-depth current measurements were undertaken in January and February 2009 across the slope and shelf in the southeastern Weddell Sea. Southwestward surface-intensified currents of ∼30 cm s−1, and northeastward undercurrents of 6–9 cm s−1, were in thermal-wind balance with the sloping isopycnals across the front, which migrated offshore by 30 km in the time interval between the two sections. A mid-depth undercurrent on February 23 was associated with a 130-m uplift of the main pycnocline, bringing Warm Deep Water closer to the shelf break. This vertical displacement, comparable to that caused by seasonal variations in wind speed, implies that undercurrents may affect the exchanges between coastal and deep waters near the Antarctic continental margins.
Keywords: Sørishavet; Weddellhavet; hydrografi; isbrem; isshelf; kontinentalmargin; kontinentalsokkel; oseanografi; understrømmer

Mixing on the continental slope of the southern Weddell Sea - Daae, Kjersti L.; Fer, Ilker; Abrahamsen, E. Povl (Journal of Geophysical Research: Oceans, 2009)
Shipboard hydrography and current profiles collected in 2003 and time series from moored current meters deployed in late 1990s are analyzed to study the variability of mixing in the southeastern Weddell Sea. Profiles of eddy diffusivity Kρ are inferred from fine-scale shear (vertical derivative of horizontal velocity) and strain (vertical derivative of isopycnal displacement) variance using parameterizations which relate the internal wave energy to the dissipation rate at small scales. The highest mixing rates are seen near the bottom where the eddy diffusivities are elevated by 1 order of magnitude from those in the interior and exceed 10−4 m2 s−1. The observations show latitudinal variability in Kρ, particularly near the bottom, where Kρ significantly increases near 74° 28′S, the critical latitude for lunar semidiurnal (M2) tides. In this region, the critical latitude coincides with near-critical topography on the upper continental slope, a situation which favors generation of M2 internal waves. Consistent with the results from fine-scale shear and strain parameterizations, which indicate highest bottom diffusivities near the critical latitude, independent analysis of current time series from moored instruments shows a thickening of the frictional bottom boundary layer near the critical latitude. Semidiurnal tidal dynamics at the upper continental slope together with the critical latitude effects lead to mixing that might significantly affect the regional heat budget and the circulation in the study area.
Keywords: Sørishavet; Weddellhavet; bunnvann; geofysikk; hydrografi; kontinentalmargin; oseanografi; vannvirvler

Crustal structure and tectonic provinces of the Riiser-Larsen Sea area (East Antarctica): results of geophysical studies - Leitchenkov, German; Guseva, J; Gandyukhin, V; Grikurov, G; Kristoffersen, Yngve; Sand, M; Golynsky, A; Aleshkova, N (Marine Geophysical Researches, 2008)
Keywords: Sørishavet; kontinentalmargin; marin geofysikk; seismologi; stratigrafi

The Cosmonaut Sea Wedge - Solli, Kenneth; Kuvaas, Berit; Kristoffersen, Yngve; Leitchenkov, German; Guseva, J; Gandyukhin, V (Marine Geophysical Researches, 2008)
Keywords: Sørishavet; kontinentalmargin; marin geofysikk; sedimenter

Glaciomarine turbidite and current controlled deposits in Prydz Bay, Antarctica - Kuvaas, Berit; Leitchenkov, German (Marine Geology, 1992)
A thick sequence (up to 2200 m) of presumed post late Eocene/early Oligocene glaciomarine sediments is inferred to be present on the Prydz Bay continental rise. In the absence of information from drillholes, we correlate to ODP Leg 119 drillsites on the shelf and compare with the seismic reflection pattern of glaciomarine sequences in the Weddell Sea. The inferred glaciomarine sediments in Prydz Bay appear to be deposited in a complex manner, suggesting interaction by both turbidity cur rents and strong bottom currents. Reflection seismic profiles from the lower continental slope and rise shows an abundance of current influenced deposits, such as sediment waves and large sediment ridges with similarities to contourite drifts. In addition, large channel-levee complexes are abundant, suggesting deposition by turbidity currents and other massflow processes. Large channels and sediment ridges trend oblique to the continental margin. The geometry and character of the seismic reflection pattern suggest that the ridges have been deposited under the combined influence of overflow from downslope channelized turbidity currents and strong bottom water flow. The observed sediment waves and the difference along eastern and western channel margins suggest that bottom currents are flowing towards the west. We suggest that the initiation of turbidite sedimentation occurred in the late Eocene-early Oligocene, when the Amery Ice Shelf reached the shelf edge for the first time. Onset of current controlled deposition may possibly be related to the opening of the Drake Passage at the Oligocene/Miocene boundary.
Keywords: Sørishavet; Weddellhavet; havbunnen; kontinentalmargin; marin geologi

The Crary Fan: A trough-mouth fan on the Weddell Sea continental margin, Antarctica - Kuvaas, Berit; Kristoffersen, Yngve (Marine Geology, 1991)
Multichannel seismic investigations show the presence of a large trough-mouth fan deposit on the continental margin in the southern Weddell Sea. A characteristic feature of the fan is relatively few, but large canyons and/or channels which appear to have been stable for long periods. Levees associated with the channels may reach thicknesses of more than 1 km. Drilling during ODP Leg 113 recorded the presence of glaciers in East Antarctica since early Oligocene time, and the seismic stratigraphic evidence suggests that the submarine fan is largely composed of glacigenic sediments. The channel-levee systems and complexes indicate several growth phases, apparently controlled by glacial/interglacial climate fluctuations, with maximum fan growth during glacial periods. The present interglacial period is characterized by strong and erosive flow of Ice Shelf Water running down the western slope of the fan and carrying only minor amounts of suspended matter. The fan is essentially sediment starved during interglacial periods. The dimensions of the channel-levee complexes and the persistent loci of sediment supply suggest that turbidite sedimentation resulted from melting of wet-based glaciers at or near the shelf edge, which has consequently prograded 70-80 km seaward.
Keywords: Sørishavet; Weddellhavet; havbunnen; isshelf; kontinentalmargin; kontinentalsokkel; marin geologi; seismologi

The Continental Margin of Queen Maud Land/Antarctica: Seismic Sequences, Structural Elements and Geological Development - Hinz, Karl; Krause, W (Geologisches Jahrbuch. Reihe E, Geophysik, 1982)
Keywords: Dronning Maud Land; geologi; kontinentalmargin; seismologi